## Intermediate Algebra (12th Edition)

$x=\left\{ -\dfrac{1}{3},-3 \right\}$
$\bf{\text{Solution Outline:}}$ Express the given equation, $3x^2+3=-10x ,$ in factored form. Then, use the Zero-Factor Property by equating each factor to zero. Finally, solve each equation. $\bf{\text{Solution Details:}}$ The factored form of the equation above is \begin{array}{l}\require{cancel} 3x^2+10x+3=0 \\\\ (3x+1)(x+3)=0 .\end{array} Equating each factor to zero (Zero-Factor Property), then \begin{array}{l}\require{cancel} 3x+1=0 \text{ OR } x+3=0 .\end{array} Using the properties of equality to solve each of the equation above results to \begin{array}{l}\require{cancel} 3x+1=0 \\\\ 3x=-1 \\\\ x=-\dfrac{1}{3} \\\\\text{ OR }\\\\ x+3=0 \\\\ x=-3 .\end{array} Hence, the solutions are $x=\left\{ -\dfrac{1}{3},-3 \right\} .$ $\bf{\text{Supplementary Solution:}}$ To factor the expression, $3x^2+10x+3 ,$ find two numbers whose product is $ac$ and whose sum is $b$ in the quadratic expression $ax^2+bx+c.$ Use these $2$ numbers to decompose the middle term of the given quadratic expression and then use factoring by grouping. In the expression above the value of $ac$ is $3(3)=9$ and the value of $b$ is $10 .$ The possible pairs of integers whose product is $ac$ are \begin{array}{l}\require{cancel} \{1,9\}, \{3,3\}, \{-1,-9\}, \{-3,-3\} .\end{array} Among these pairs, the one that gives a sum of $b$ is $\{ 1,9 \}.$ Using these $2$ numbers to decompose the middle term of the trinomial expression above results to \begin{array}{l}\require{cancel} 3x^2+1x+9x+3 .\end{array} Grouping the first and second terms and the third and fourth terms, the given expression is equivalent to \begin{array}{l}\require{cancel} (3x^2+1x)+(9x+3) .\end{array} Factoring the $GCF$ in each group results to \begin{array}{l}\require{cancel} x(3x+1)+3(3x+1) .\end{array} Factoring the $GCF= (3x+1)$ of the entire expression above results to \begin{array}{l}\require{cancel} (3x+1)(x+3) .\end{array}